Machine learning with R quick start guide : a beginner's guide to implementing machine learning techniques from scratch using R 3.5 - Pastor Sanz, Iván (Packt Publishing, 2019)
This book is ideal for people wanting to get up-and-running with the core concepts of machine learning using R 3.5. This book follows a step-by-step approach to implementing an end-to-end pipeline, addressing data collection and processing, various types of data analysis, and machine learning use cases.